EFFECT OF SEASON AND STAGE OF LACTATION ON MILK COMPONENTS OF JAFFRABADI BUFFALOES - T. K. PATBANDHA; K. RAVIKALA; B. R. MAHARANA; S. MARANDI; A. R. AHLAWAT; P. U. GAJBHIYE (The Bioscan, 2015)
The present study was designed to see the effect of season and lactation stage on milk components of Jaffrabadi buffaloes. Total 900 milk samples were collected, comprised of 100 samples each from season (winter, summer and rainy) and from lactation stage (early, mid and late) for the study. Overall milk fat, protein, lactose, ash, solid not fat (SNF) and total solids (TS) were observed to be 8.31±0.37, 4.31±0.06, 5.66±0.09, 0.96±0.01, 10.93±0.18 and 19.24±0.43%, respectively. There was significantly (P<0.05) higher protein percent during rainy and lower during winter (4.37±0.05 and 4.20±0.05%, respectively), but milk lactose percent was significantly (P<0.05) higher during winter (5.46±0.07%) and lower during rainy (5.79±0.07%). Stage of lactation had also significant effect on milk components; milk fat, protein and TS percent increased significantly with the advancement of lactation stage; whereas, milk lactose decreased significantly (P<0.05). Milk fat during early, mid and late lactation was 7.65±0.10, 8.36±0.10 and 8.92±0.11%; protein was 4.25±0.04, 4.24±0.05 and 4.44±0.05% and TS was 18.7±0.18, 19.02±0.20 and 19.85±0.22%, respectively (P<0.05). However, milk lactose percent was 5.83±0.06, 5.65±0.07 and 5.51±0.07%, respectively during early, mid and late lactation (P<0.05). Thus, results of the present investigation indicated that season and stage of lactation affect certain milk components in Jaffrabadi buffaloes and could be minimized by better farm management practices.